Beitragsnovellierung in der landwirtschaftlichen Unfallversicherung - Notwendigkeit und Vorschlag̈e - Enno Bahrs (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Amendment of the Premiums for the Agrarian Accident InsuranceMany German farmers do no longer accept the annual premiums for the state accident insurance, which sometimes reach a considerable degree. The farmers are of the opinion that the specific accident risk of each farm has to be taken into account. So far, the agrarian professional associations as representatives of the state accident insurance, predominantly measure the premium standards by acre/ hectare which no longer fulfils the equivalence principle.The merger of some agrarian professional associations, which take place at present or are planned in the near future, should be regarded as an opportunity to institutionalize new and more appropriate premium standards. They have to be adapted anyway, as a merger usually means the standardization of two or more different premium standards. Inevitably there will be redistributions of the premium burden. The present time is ideal to use simultaneously a premium standard that is viable in the future. This essay analyses the predominantly used premium standards and suggests appropriate methods to measure future standards.
Keywords: 330; Landwirtschaft; Unfallversicherung; Versicherungsbeitrag; Äquivalenzprinzip; Deutschland